A systematic review of non-motor rTMS induced motor cortex plasticity - Nordmann, Gregory; Azorina, Valeriya; Langguth, Berthold; Schecklmann, Martin (Frontiers in Human Neuroscience, 2015)
Motor cortex excitability can be measured by single- and paired-pulse transcranial magnetic stimulation (TMS). Repetitive transcranial magnetic stimulation (rTMS) can induce neuroplastic effects in stimulated and in functionally connected cortical regions. Due to its ability to non-invasively modulate cortical activity, rTMS has been investigated for the treatment of various neurological and psychiatric disorders. However, such studies revealed a high variability of both clinical and neuronal effects induced by rTMS. In order to better elucidate this meta-plasticity, rTMS-induced changes in motor cortex excitability have been monitored in various studies in a pre-post stimulation design. Here, we give a systematic literature review (April 2014) of 29 studies investigating motor cortex excitability changes as a neuronal marker for rTMS effects over non-motor cortical areas. The majority of the studies focused on the stimulation of one of three separate cortical areas: the prefrontal area (17 studies), the cerebellum (8 studies), or the temporal cortex (3 studies). One study assessed the effects of multi-site rTMS. Most studies investigated healthy controls but some also stimulated patients with neuropsychiatric conditions (e.g., affective disorders, tinnitus). Methods and findings of the identified studies were highly variable showing no clear systematic pattern of interaction of non-motor rTMS with measures of motor cortex excitability. Based on the available literature, the measurement of motor cortex excitability changes before and after non-motor rTMS has only limited value in the investigation of rTMS related meta-plasticity as a neuronal state or as a trait marker for neuropsychiatric diseases. Our results do not suggest that there are systematic alterations of cortical excitability changes during rTMS treatment, which calls into question the practice of re-adjusting the stimulation intensity according to the motor threshold over the course of the treatment